1993
DOI: 10.1063/1.108608
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer scale patterning of a monolayer Langmuir–Blodgett film with a scanning tunneling microscope in air

Abstract: Nanometer scale patterns have been fabricated on a Langmuir–Blodgett deposited monolayer film of stearic acid using a scanning tunneling microscope in air. Carbon deposits build up underneath the tip for tip voltages with absolute value greater than 4 V. Using an atomic force microscope for image, lines 25 nm wide on a 60 nm period have been written. As confirmed with Auger electron spectroscopy, the unexposed film can be removed with a chloroform soak without affecting the existing carbon patterns, and no add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…For example, spincoated polymer films and Langmuir-Blodgett films have been patterned using scanning tunneling microscopes (STMs) operated in vacuum [6 -8] as well as by using STMs or atomic force microscopes (AFMs) operated in air [9,10].…”
Section: *Present Address: Departmentmentioning
confidence: 99%
“…For example, spincoated polymer films and Langmuir-Blodgett films have been patterned using scanning tunneling microscopes (STMs) operated in vacuum [6 -8] as well as by using STMs or atomic force microscopes (AFMs) operated in air [9,10].…”
Section: *Present Address: Departmentmentioning
confidence: 99%
“…Fluowet SB is regularly used as a spreading agent. [15] The complexation of PEI with Fluowet SB (stoichiometric complex with respect to charge) was performed in water by adding solutions of PEI to a dilute micellar solution of Fluowet SB. In contrast to the procedure described earlier, [12,13] macroscopic precipitation of the complex was avoided by using an excess of Fluowet SB to aid dispersion.…”
mentioning
confidence: 99%
“…These results are consistent with our former work on the stearic acid-Au system where the material buildup under the tip was confirmed to be carbon by Auger electron spectroscopy. 1 This process appears to be very similar to the buildup of lines of contamination in vacuum in the presence of a focused electron beam 13 where the resulting high-molecular-weight hydrocarbon is insoluble in most solvents. It was also found that the average linewidth of these carbon patterns decreased as the tunneling current decreased.…”
Section: Resultsmentioning
confidence: 90%
“…[1][2][3][4] The advantage of the LB technique is that organic monolayers can be formed on most substrates. Sub-100-nm lines have been written in a trilayer of decosenoic acid ͑film thickness 10 nm͒ using a high-vacuum scanning tunneling microscope ͑STM͒ for exposure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation